Atomic structure of water/Au, Ag, Cu and Pt atomic junctions. Issue 6 (26th January 2017) - Li, Yu; Kaneko, Satoshi; Fujii, Shintaro; Nishino, Tomoaki; Kiguchi, Manabu
Abstract : The atomic and electrical conductance of single water molecule–Au, Ag, Cu and Pt junction systems were investigated at low temperatures using a mechanically controllable break junction technique. Abstract : Much progress has been made in understanding the transport properties of atomic-scale conductors. We prepared atomic-scale metal contacts of Cu, Ag, Au and Pt using a mechanically controllable break junction method at 10 K in a cryogenic vacuum. Water molecules were exposed to the metal atomic contacts and the effect of molecular adsorption was investigated by electronic conductance measurements. Statistical analysis of the electronic conductance showed that the water molecule(s) interacted with the surface of the inert Au contact and the reactive Cu ant Pt contacts, where molecular adsorption decreased the electronic conductance. A clear conductance signature of water adsorption was not apparent at the Ag contact. Detailed analysis of the conductance behaviour during a contact-stretching process indicated that metal atomic wires were formed for the Au and Pt contacts. The formation of an Au atomic wire consisting of low coordination number atoms leads to increased reactivity of the inert Au surface towards the adsorption of water.